PATHOGENIC POTENTIAL OF Vibrio parahaemolyticus ISOLATED FROM TROPICAL ESTUARINE ENVIRONMENTS IN CEARÁ, BRAZIL - Gleire Rodrigues de Menezes, Francisca; Silva Neves, Soraya; dos Santos Rocha, Rafael; Viana Sousa, Oscarina; Teresa Rodriguez Torres, Marina; Maggioni, Rodrigo; Hofer, Ernesto; Helena Silva dos Fernandes Vieira, Regine (Revista de Patologia Tropical / Journal of Tropical Pathology, 2020)
Vibrio parahaemolyticus is a potentially pathogenic bacterium that occurs naturally in estuarine environments worldwide. This research aimed to investigate the occurrence of Vibrio parahaemolyticus in estuarine environments and determine the virulence profile in aquaculture environment by molecular techniques and conventional microbiological methods. The analysis included 64 samples of water (n=32) and sediment (n=32) collected in estuaries. The samples yielded 64 strains suspected to be V. parahaemolyticus. The isolates were submitted to biochemical identification using a dichotomous key and PCR for the detection of the species-specific gene tl. Virulence was assessed by testing for urea hydrolysis and ?-hemolysis in erythrocytes (Kanagawa phenomenon) and simultaneous detection of the genes tdh and trh. All but one of the isolates (63/64) were confirmed to be V. parahaemolyticus by genotypic detection of tl. The genes tdh and trh were detected in 57 and 19 isolates, respectively. The Kanagawa test was positive for 51 isolates. Only one isolate was positive for urease. The incidence of tdh/trh-positivity was very high in strains isolated from the environment. The present study demonstrates that the necessity to improve the knowledge of the ecology and pathogeny of V. parahaemolyticus.